Monophyly, review, six new species and DNA barcode of micropterous Afromontane Afropictinus (Heteroptera: Aradidae) - Heiss, Ernst; Grebennikov, Vasily (Zootaxa, 2016)
The micropterous East African flat bug genus Afropictinus Heiss, 1986 (Heteroptera: Aradidae: Mezirinae) is revised. In addition to the type and only known species A. congoensis (Hoberlandt, 1956) from Rwanda, four new species from Tanzania (A. castor sp. nov., A. hylas sp. nov., A. idas sp. nov., A. nauplius sp. nov.), one new species from the Democratic Republic of the Congo (A. kahuzianus sp. nov.), and one new species from Ethiopia (A. nabu sp. nov.) are described and illustrated. An identification key is presented to all seven nominal species of Afropictinus. DNA barcodes of 28 individuals of Afropictinus species were newly generated and together with 12 sequences of other Aradidae were made publicly available at dx.doi.org/10.5883/DS-AFROPICT. These mtDNA sequences were analyzed phylogenetically using Maximum Likelihood approach with 500 bootstraps. Obtained topology reveals a monophyletic Afropictinus with high statistical support (84%), although its sister group remains elusive. Both specimens of non-Tanzanian Afropictinus species included in the study (A. kahuzianus and A. nabu) were nested among Tanzanian congeners. The internal clades within Afropictinus, except for those at species and population level, had lesser statistical support. Despite of intense sampling, no Afropictinus species was found in mountain forests of geologically young (<2 Ma) volcanic highlands of the Ngorongoro-Kilimanjaro Volcanic Belt, which suggest reduced dispersal capacities.